Finding Common Ground: A Critical Review of Land Use and Resource Management Policies in Ontario, Canada and their Intersection with First Nations - McLeod, Fraser; Viswanathan, Leela; Whitelaw, Graham S.; Macbeth, Jared; King, Carolyn; McCarthy, Daniel D.; Alexiuk, Erin (International Indigenous Policy Journal, 2015)
This article provides an in-depth analysis of selective land use and resource management policies in the Province of Ontario, Canada. It examines their relative capacity to recognize the rights of First Nations and Aboriginal peoples and their treaty rights, as well as their embodiment of past Crown–First Nations relationships. An analytical framework was developed to evaluate the manifest and latent content of 337 provincial texts, including 32 provincial acts, 269 regulatory documents, 16 policy statements, and 5 provincial plans. This comprehensive document analysis classified and assessed how current provincial policies address First Nation issues and identified common trends and areas of improvement. The authors conclude that there is an immediate need for guidance on how provincial authorities can improve policy to make relationship-building a priority to enhance and sustain relationships between First Nations and other jurisdictions.